2011
DOI: 10.3390/pharmaceutics3030338
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Vector-Derived VA-RNA-Mediated Innate Immune Responses

Abstract: The major limitation of the clinical use of replication-incompetent adenovirus (Ad) vectors is the interference by innate immune responses, including induction of inflammatory cytokines and interferons (IFN), following in vivo application of Ad vectors. Ad vector-induced production of inflammatory cytokines and IFNs also results in severe organ damage and efficient induction of acquired immune responses against Ad proteins and transgene products. Ad vector-induced innate immune responses are triggered by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 100 publications
0
36
0
Order By: Relevance
“…VA-RNAs block PKR activation, leading to inhibition of phosphorylation of eIF2α and efficient replication of Ad815. In order to examine whether an increase in the copy numbers of VA-RNA by Dicer knockdown leads to a reduction in Ad-induced phosphorylation of eIF2α, HeLa-shDicer cells were cultured in the presence or absence of Dox (100 ng ml −1 ), followed by infection with WT-Ad or Sub720.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VA-RNAs block PKR activation, leading to inhibition of phosphorylation of eIF2α and efficient replication of Ad815. In order to examine whether an increase in the copy numbers of VA-RNA by Dicer knockdown leads to a reduction in Ad-induced phosphorylation of eIF2α, HeLa-shDicer cells were cultured in the presence or absence of Dox (100 ng ml −1 ), followed by infection with WT-Ad or Sub720.…”
Section: Resultsmentioning
confidence: 99%
“…The adenovirus (Ad) genome also encodes two noncoding small RNAs, VA-RNA I (a major species) and VA-RNA II (a minor species), which are approximately 160 nucleotide-long noncoding RNAs that are transcribed by RNA polymerase III78. VA-RNA I is rapidly transcribed after infection and accumulates to very high levels, 10 8 molecules per cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…injection of adenovirus vectors results in hepatic tropism, making it difficult to systemically deliver adenovirus vectors for metastasis treatment . Third, the strong immunogenic nature of adenoviruses seriously hampers their efficacy and safety in vivo . Fourth, clinical studies on oncolytic adenoviruses have suggested that several modifications are necessary to enhance the oncolytic activity and improve safety in the clinical setting .…”
mentioning
confidence: 99%
“…Ad expresses Ad-encoded small noncoding RNAs (VA-RNAs), which inhibit production of miRNAs (15)(16)(17)(18)(19)(20)(21)(22)(23). VA-RNAs were originally demonstrated to inhibit double-stranded RNA-dependent kinase (PKR), leading to efficient translation of viral proteins (24)(25)(26)(27); more recently, however, VA-RNAs were reported to inhibit miRNA production (15)(16)(17)(18)(19)(20)(21)(22)(23). VA-RNAs inhibit Dicer expression by inhibiting nuclear export of Dicer mRNA, leading to suppression of miRNA production (15).…”
mentioning
confidence: 99%